Hormônios e percepção auditiva: estudo da escuta dicótica em mulheres durante o ciclo menstrual - Carneiro, Cláudia da Silva (2016)
Fluctuations in the levels of gonadal steroid hormones during the menstrual cycle may influence, among other issues, the auditory information processing in the brain. However, the specific mechanisms have not been fully elucidated and the results are controversial. This study purposed to investigate the auditory perception in women during the menstrual cycle. In this research we developed two articles: the first is a systematic review entitled "auditory perception evaluation in women during the menstrual cycle: a systematic review", which purposed to pursue studies that show the relationship between hormones and auditory perception. The final sample of this systematic review consisted of seven articles. It was found that gonadal steroid hormones can interfere with the auditory perception of women, pointing to the dichotic tests as the one used for assessing auditory perception in this population. This article has been submitted for publication in the Journal of Otolaryngology. The second article was developed with empirical data from field research, which aimed to investigate the dichotic listening women during the menstrual cycle. The participants were 20 volunteers, 09 female and 11 male. They underwent a basic audiological evaluation, blood plasma collection (women only) and evaluation of dichotic listening through three behavioral tests: dichotic SSW, dichotic digits and consonant-vowel. There was improved performance of the right ear in the follicular phase of the menstrual cycle for the SSW test, with significant results. Moreover, when the ears were compared at each stage, there is better performance right ear in both phases and groups for the consonant-vowel pattern, showing significant results. This article will be submitted to codas journal.